Pelatihan Bantuan Hidup Dasar Bagi Masyarakat Awam: Pengabdian - Kok Mesa, Nofita Dewi; Warimilena , Soleman; Sasari, Yamamoto; Baransano, Yulyanus; Tarigan, Nelson; Suprayitno, Guruh; Tanawani, Pithein (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Cardiac arrest is a condition of emergency that often occurs. Cardiac arrest is the leading cause of death in many countries. Worldwide patient survival rates after OHCA are still poor. Death from cardiac arrest can occur within minutes if the victim does not receive intervention. Early initiation related to Cardiopulmonary Resuscitation (RJP) by people around the patient is one of the main factors in saving patients with cardiac arrest, so it is very important to train ordinary people in Basic Life Assistance measures. The purpose of this community service is so that the community can understand and demonstrate the actions of Basic Life Assistance (BHD) properly and correctly. The method is carried out by providing education and simulation training directly on basic life support. The results obtained were that 73 people in groups were able to demonstrate BHD properly and correctly.